2015
DOI: 10.1021/acs.analchem.5b00228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graphene-Nanoplatelets Structure via Thermogravimetry

Abstract: The rapid increase in graphene-based applications has been accompanied by novel top-down manufacturing methods for graphene and its derivatives (e.g., graphene nanoplatelets (GnPs)). The characterization of the bulk properties of these materials by imaging and surface techniques (e.g., electron microscopy and Raman spectroscopy) is only possible through laborious and time-consuming statistical analysis, which precludes simple and efficient quality control during GnP production. We report that thermogravimetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 33 publications
9
62
0
1
Order By: Relevance
“…The thermal stability of GNP, and hence a further qualitative evaluation of its defectiveness, was evaluated by TGA in air ( Figure 2d); in fact, it was reported that size and defectiveness, of graphenerelated materials, affect the onset of decomposition temperature [54]. The thermogram of the GNP used in this study exhibits two degradation steps: in the first, weight loss of about 6 wt.% occurred between ~ 450°C and 600°C, which could be related to smaller and highly defective nanoparticles; whereas in the second step a further 80 wt.% loss is verified between ~ 600°C and 850°C, with the maximum of mass loss rate centered at ~ 762 °C and about 11 wt.% residue at 850°C, thus indicating an high content of large and low defective nanoflakes, according to the work of Shtein et al [54]. This is crucial for the obtainment of highly thermally conductive polymer nanocomposites.…”
Section: Nanoflakes Characterizationmentioning
confidence: 99%
“…The thermal stability of GNP, and hence a further qualitative evaluation of its defectiveness, was evaluated by TGA in air ( Figure 2d); in fact, it was reported that size and defectiveness, of graphenerelated materials, affect the onset of decomposition temperature [54]. The thermogram of the GNP used in this study exhibits two degradation steps: in the first, weight loss of about 6 wt.% occurred between ~ 450°C and 600°C, which could be related to smaller and highly defective nanoparticles; whereas in the second step a further 80 wt.% loss is verified between ~ 600°C and 850°C, with the maximum of mass loss rate centered at ~ 762 °C and about 11 wt.% residue at 850°C, thus indicating an high content of large and low defective nanoflakes, according to the work of Shtein et al [54]. This is crucial for the obtainment of highly thermally conductive polymer nanocomposites.…”
Section: Nanoflakes Characterizationmentioning
confidence: 99%
“…Furthermore, the second-order spectrum for both rGO shows a narrower and more intense G' peak at ~2705 cm -1 . temperature plot, Figure S2), to indirectly investigate their structural features, knowing that the onset decomposition temperature can be qualitatively related to the size and the defectiveness of graphenerelated materials [35]. T onset (Table 1) for GNP was measured at 632°C, whereas significantly lower values were obtained for RGO (558°C) and RGO-2 (471°C).…”
Section: Nanoflakes Characterizationmentioning
confidence: 99%
“…We started from non‐aromatic compounds (e.g., NaCl) and non‐conjugated aromatics (e.g., polystyrene), and proceeded through semi‐conjugated aromatics (e.g., dibenzo crown ether and diphenylbutadiyne) to fully conjugated aromatics (e.g., naphthalene, anthracene, and pyrene) ( Figure ). The more conjugated (and planar) the diluent, the stronger its adsorption to and protection of the graphitic surface from converting to amorphous carbon, as analyzed by thermogravimetric analysis (TGA) (Figure b, and Section S3.1, Supporting Information). TGA parameters, such as T 1/2 , the temperature of the combustion step at which half of the total weight loss is reached (Section S3.1, Supporting Information), is correlated with both the graphene sheet dimensions (thickness and mean lateral dimension (MLD), Section S4, Supporting Information) and the defect density .…”
mentioning
confidence: 99%
“…The more conjugated (and planar) the diluent, the stronger its adsorption to and protection of the graphitic surface from converting to amorphous carbon, as analyzed by thermogravimetric analysis (TGA) (Figure b, and Section S3.1, Supporting Information). TGA parameters, such as T 1/2 , the temperature of the combustion step at which half of the total weight loss is reached (Section S3.1, Supporting Information), is correlated with both the graphene sheet dimensions (thickness and mean lateral dimension (MLD), Section S4, Supporting Information) and the defect density . Additional TGA parameter is Δ T , the temperature range in which the graphene sheets burn (Sections S3.1 and S4, Supporting Information) is related to the polydispersity of the graphene products …”
mentioning
confidence: 99%
See 1 more Smart Citation